2009
DOI: 10.1108/17538270910963090
|View full text |Cite
|
Sign up to set email alerts
|

Housing price determinants in Istanbul, Turkey

Abstract: PurposeThe purpose of this paper is to analyze empirically major factors that affect housing prices in Istanbul, Turkey using the classification and regression tree (CART) approach.Design/methodology/approachThe data set was collected from various internet pages of real estate agencies during June 2007. The CART approach was then applied to derive main results and to make implications with regard to the housing market in Istanbul, Turkey.FindingsThe CART results indicate that sizes, elavators, existance of sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…is application is developed for the Singapore resale public housing market. However, although the process used to identify the main variables that affect the price of housing is extensive, its estimation is based solely on the average value in a leaf node of the tree, this value being thought of as a forecasting value or regression value.Özsoy and Şahin [23] develop a CART application in Turkey to determine the most influential characteristics on the price of housing in Istanbul based on a database taken from the Internet in 2007. e results lead them to conclude that the size of the house and the existence of an elevator, security, central heating, and views are the most influential variables on house prices in Istanbul.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…is application is developed for the Singapore resale public housing market. However, although the process used to identify the main variables that affect the price of housing is extensive, its estimation is based solely on the average value in a leaf node of the tree, this value being thought of as a forecasting value or regression value.Özsoy and Şahin [23] develop a CART application in Turkey to determine the most influential characteristics on the price of housing in Istanbul based on a database taken from the Internet in 2007. e results lead them to conclude that the size of the house and the existence of an elevator, security, central heating, and views are the most influential variables on house prices in Istanbul.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ese same aspects are highlighted in [55,56] in which the authors point out that web prices offer a valuable opportunity for statistical analysis due to the constant generation of information, their accessibility, and availability as well as there being little notable differences compared to offline prices. Within real estate, applications developed using web data are used byÖzsoy and Şahin [23] in Istanbul; Del Cacho [14] in Madrid; Larraz and Larraz and Población [57,58] in Spain; Pow et al [17] in Montreal; Larraz and Población [59] in Czech Republic; Nguyen [25] in the United States; Clark and Lomax [36] in England; Pérez-Rave et al [20] in Colombia; or Neloy et al [44] in Bangladesh.…”
Section: Empirical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main conclusion is that houses are not overpriced in Sweden. Ozsoy and Sahin (2009) analyze the factors affecting housing prices in Istanbul, Turkey. They found that beside location/area, the most dominating factors in the determination of house prices are sizes, elevators, available security measures, existence of central heating units and view of the house.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of the study during which non-residential consumption and residence expense data were used, Piazzesi, Schneider and Tuzel (2007) created an equilibrium model to estimate the residence prices. Ozsoy and Sahin (2009) have used the classification and regression tree (CART) approach in order to examine the essential parameters that affect the residence prices in Istanbul. As a result of this study, the area, elevator, security, central heating system and facade parameters have been determined to be the most important criteria for the residence prices in Istanbul.…”
Section: Introductionmentioning
confidence: 99%